Sirolimus for the treatment of polyposis of the rectal remnant and ileal pouch in four patients with familial adenomatous polyposis: a pilot study - Evelien Dekker; Lianne Koens; Barbara A J Bastiaansen; Victorine H Roos; Bartolomeus J Meijer; Frank G J Kallenberg; Frederike J Bemelman; Patrick M M Bossuyt; Jarom Heijmans; Gijs van den Brink (BMJ Open Gastroenterology)
Objective After prophylactic colectomy, adenomas continue to develop in the remaining intestine of patients with familial adenomatous polyposis (FAP). There is a lack of standard clinical recommendation for chemoprevention in patients with FAP. Because of promising in vivo studies, the aim of this pilot study was to investigate the safety of sirolimus and its effect on progression of intestinal adenomas.Design Patients with FAP with InSiGHT Polyposis Staging System 3 of the retained rectum or pouch received sirolimus for 6 months, dosed at plasma concentration levels of 5–8 µg/L. Primary outcomes were safety and change in marked polyp size. Secondary outcomes were change in number of polyps and effect on proliferation and apoptosis assessed by immunohistochemistry.Results Each of the included four patients reported 4 to 18 adverse events (toxicity grades 1–3). One patient prematurely terminated the study because of adverse events. Marked polyp size decreased in 16 (80%)/20 and remained the same in 4 (20%)/20 patients. The number of polyps decreased in all patients (MD −25.75, p=0.13). Three out of four patients showed substantial induction of apoptosis or inhibition of proliferation.Conclusion Six months of sirolimus treatment in four patients with FAP showed promising effects especially on the number of polyps in the rectal remnant and ileal pouch, although at the cost of numerous adverse events.Trial registration number ClinicalTrials.gov ID NCT03095703.